Gestión de los ingresos y gastos en el periodo 2019 y 2020 de la empresa Corporación de Seguridad Mares Ecu Corsemaecu Cia.Ltda - Gil Teran, Kevin Javier (2021)
The Mares Security Corporation Ecu Corsemaecu Cia.Ltda. With RUC # 0993196479001, it is located at calle b no. 3404 (calle k and calle l) in Babahoyo is an institution that among its main activities has to provide guardianship and patrol services, it is in a private for-profit status and has as main clients public institutions both inside and outside the province. This institution has a wide range of services, including guardianship and patrol services, but it also provides security systems services, investigation services, and armored vehicle services. This research will take into account the income obtained in 2019 by the Corporación De Seguridad Mares Ecu Corsemaecu Cia.Ltda, legitimately established in the province of Los Ríos, parent company in Babahoyo, its activity is to provide good service to customers already the users of the same. The guardian service is carried out, both towards institutions of the public and private sectors, seeking the welfare of the users and the conservation of the assets of said institutions. The administrative part of the corporation, being a young institution, does not yet have a system for the management of economic activity, which is developed in the free Excel program, which develops a basic control of the income and expenses that it has for the decision-making of the partners in the company.